Students’ preferences and challenges in learning English fully online with Google Classroom - Sri Wahyuni; Fauzul Etfita; Nadya Alkhaira (Journal of Education and Learning (EduLearn), 2022)
The Coronavirus 2019 outbreak caused the world to experience a pandemic and paralyze human activities, including the education sector. Consequently, the teaching-learning system changed from face-to-face to online. This study aimed to determine how high school students' preferences and challenges in Pekanbaru city employing the Google Classroom to learn English. This descriptive study involved 30 high school and vocational high school students as the sample who obtained through purposive sample technique. Google Form and interviews with Zoom were employed to gather the data. This study found that Google Classroom was quite effective in helping students replace the learning process during a pandemic with an online learning system.